Tai Ji Quan as an exercise modality to prevent and manage cardiovascular disease: A review - Ruth E. Taylor-Piliae (Elsevier, 2014)
Background: Regular exercise is beneficial for adults with cardiovascular disease (CVD) and CVD risk factors. Tai Ji Quan is popular among older adults and may offer additional exercise options. The present article aims to review the scientific literature published within the past decade on Tai Ji Quan as an exercise modality to prevent and manage CVD. Methods: An electronic literature search of four databases (PubMed, CINAHL, PsycINFO, and AMED) was conducted from April 2003 through March 2013. Studies that examined Tai Ji Quan, were published in English, and specified a target study population of participants with a known CVD condition (e.g., coronary artery disease, chronic heart failure, or stroke) or studies conducted among participants with a CVD risk factor (e.g., hypertension, dyslipidemia, or impaired glucose metabolism) were included. Results: A total of 20 studies met the inclusion criteria: 11 randomized clinical trials, seven quasi-experimental studies and two cross-sectional studies. The effect of Tai Ji Quan was examined on more than 20 different study variables among persons with coronary artery disease (n = 5 studies), chronic heart failure (n = 5 studies), stroke (n = 4 studies), and CVD risk factors (n = 6 studies). These studies were conducted primarily in Asia (n = 9, 45%) or the United States (n = 8, 40%). Overall, participants enrolled in Tai Ji Quan had better outcomes, though mixed results were reported. Conclusion: Collectively, these studies indicate that Tai Ji Quan is a safe form of exercise to prevent and manage CVD. Further research is needed with more rigorous study designs, larger sample sizes, adequate Tai Ji Quan exercise doses, and carefully chosen outcome measures that assess the mechanisms as well as the effects of Tai Ji Quan, before widespread recommendations can be made.